Post-concussive Dizziness: A Review and Clinical Approach to the Patient - Gianoli, Gerard J. (Frontiers in Neurology, 2022)
The author operates one of the most extensive vestibular testing laboratories in the US and has nearly 30 years’ experience in the evaluation and treatment of PCD. Due to this unique tertiary care situation, the author’s perspective consists of patients with PCD of many years duration that have failed traditional treatment/rehabilitation techniques. This paper represents his views on evaluation and management. Specifically, it makes the following points: 1.) Dizziness is a quite common symptom of concussion, 2.) there is significant histologic and audio-vestibular testing evidence that head injuries frequently cause inner ear pathology, 3.) PCD patients with fixed vestibular lesions should see significant improvement/resolution of their symptoms within 3-6 months with typical vestibular rehabilitation measures, 4.) Those patients who continue to have PCD beyond this point deserve in depth audio-vestibular testing, 5.) Most PCD patients with persistent symptoms beyond 3-6 months have fluctuating vestibular disorders, 6.) A discussion of the authors approach to these chronic PCD patients who have failed traditional vestibular rehabilitation.